PENGUKUR LEVEL KETINGGIAN CAIRAN PADA KOLAM BERBASIS MIKROKONTROLER ATMEGA8 - , LEILA NURFITRIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Liquid level gage has been developed to measure the height of the liquid surface. In this final project the measuring level instrumentation used DC voltage of the battery directly, without converting from AC voltage, so it does not require a voltage PLN 220 volts. This instrumentation was developed to function as a temporary data storage (back-up data) if center data storage is experiencing problems, so the measurement level can still be controlled from the field. The sensor used is a potentiometer with a purpose that it can be used on corrugated media by using a float as the measuring medium. Then the changes of résistance value of potentiometer will be processed in the microcontroller ATmega8, so the results can be displayed on LCD. In addition, 50 recent data will be stored and can be retrieved to recapitalize measurement data, so that the operator does not need to record any changes because the data has been stored in the EEPROM of microcontroller.